A MORE REALISTIC RTP/RTCP-BASED SIMULATION PLATFORM FOR VIDEO STREAMING QoS EVALUATION - BORONAT, FERNANDO; MONTAGUD, MARIO; VIDAL, VICENT (Journal of Mobile Multimedia, 2011)
Over the last few years, the demand for real-time multimedia services has been growing progressively so that video streaming applications are expected to be dominant in future communications systems, and most of them using RTP/RTCP protocols. This paper presents an evolved tool-set for video streaming QoS evaluation in simulated environments using such protocols. We have designed a new NS-2 module with a full RTP/RTCP implementation (following strictly the RFC 3550) and we propose to combine it with additional multimedia tools to obtain an advanced simulation framework that allows the measurement of network-level QoS metrics (such as throughput, delay, jitter or loss rate) in simulation time. Besides, as the transmitted video files can be reconstructed and played out at the receiver side, the measurement of the quality of the delivered video streams, by employing the most common objective quality metrics (such as PSNR, SSIM or VQM) or subjective metrics (MOS), is also supported. By using this tool-set, researchers and practitioners can assess their novel designs (such as network protocols, routing strategies or video coding mechanisms) for such applications in heterogeneous scenarios over different network conditions. As RTCP feedback capabilities have been added, source based control techniques (such as rate adaptability or Multiple Description Coding) could be included and tested using this more realistic and powerful simulation platform.